2009
DOI: 10.1074/jbc.m109.037119
|View full text |Cite
|
Sign up to set email alerts
|

Limited Role for the Bilirubin-Biliverdin Redox Amplification Cycle in the Cellular Antioxidant Protection by Biliverdin Reductase

Abstract: In mammalian cells, heme is degraded by heme oxygenase to biliverdin, which is then reduced to bilirubin by biliverdin reductase (BVR). Both bile pigments have reducing properties, and bilirubin is now generally considered to be a potent antioxidant, yet it remains unclear how it protects cells against oxidative damage. A presently popular explanation for the antioxidant function of bilirubin is a redox cycle in which bilirubin is oxidized to biliverdin and then recycled by BVR. Here, we reexamined this putati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
64
0

Year Published

2010
2010
2022
2022

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 88 publications
(65 citation statements)
references
References 48 publications
1
64
0
Order By: Relevance
“…We propose the idea that GPS pathophysiology may be in part related to a suppressed hBVR activity and/or expression in the affected tissues that would result both in an attenuated ability to temper GPBP kinase activity and to generate the quencher of oxygen radicals, bilirubin (30). ROS have been shown to expose cryptic epitopes associated with autoimmune GPS (35) Furthermore, GPBP has been identified as a product of a human-specific TNF-␣-responsive transcriptional unit (4) and has been implicated in apoptotic pro-autoimmune signaling (44).…”
Section: Discussionmentioning
confidence: 99%
“…We propose the idea that GPS pathophysiology may be in part related to a suppressed hBVR activity and/or expression in the affected tissues that would result both in an attenuated ability to temper GPBP kinase activity and to generate the quencher of oxygen radicals, bilirubin (30). ROS have been shown to expose cryptic epitopes associated with autoimmune GPS (35) Furthermore, GPBP has been identified as a product of a human-specific TNF-␣-responsive transcriptional unit (4) and has been implicated in apoptotic pro-autoimmune signaling (44).…”
Section: Discussionmentioning
confidence: 99%
“…34 Oxidation of bilirubin partly yields biliverdin, which is rapidly reduced back to bilirubin, but irreversible oxidation to other products also occurs. 35 These compounds, which are thought to promote vasospasm, are rapidly excreted in the urine. 36 However, in the present study, there was no distinct correlation with the inflammation marker hsCRP (Tables 4 and 5).…”
Section: Discussionmentioning
confidence: 99%
“…A multitude of studies have implicated Nrf2 in the induction of HO-1 during oxidative stress (Alam et al, 2003;Gong and Cederbaum, 2006a;Gong and Cederbaum, 2006b;Sun Jang et al, 2009). Finally, in two studies looking at the effects of oxidative stress (by hydrogen peroxide treatment), it was found that cell viability was only marginally affected (Baranano et al, 2002) or not affected at all (Maghzal et al, 2009) by silencing BVR (with interference RNA). The latter study also showed that BVR induction and over-expression also did not provide protection to the cells exposed to hydrogen peroxide.…”
Section: Anti-oxidant Protectionmentioning
confidence: 99%
“…Thus, BVR may have an important role in extending the antioxidant potency of bilirubin. It should be noted that a recent study concluded that the cytoprotective role of this redox cycle was limited as BVR overexpression and inhibition of BVR expression with antisense RNA did not seem to influence hydrogen peroxide-mediated cytotoxicity (Maghzal et al, 2009). It is now known that BVR also functions as a dual-specific kinase of serine/threonine and tyrosine residues in proteins, and in this capacity, BVR affects the signaling and cellular responses to a variety of stimuli (Reviewed in (Kapitulnik and Maines, 2009)).…”
Section: Bvr-catalyzed Redox Cycle With Lipid Peroxidesmentioning
confidence: 99%